2019
DOI: 10.1007/s10900-019-00645-6
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Cervical Cancer Education: Changes in Knowledge and Beliefs Among Vietnamese American Women

Abstract: Low cervical cancer screening rates among Vietnamese American women have been attributed, in part, to inadequate knowledge about cervical cancer and health beliefs that hinder screening. A community-based educational program was developed to improve knowledge and attitudes toward cervical cancer screening in this underserved population. It was hypothesized that the program would result in increases in knowledge, as well as enhanced health beliefs and self-efficacy toward obtaining cervical cancer screening. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…In this present study, there was an increased knowledge in post-test 83.06% (p < 0.05) after introducing SIM when compared to pre-test 28.83%. Previous studies consistent with the result conducted in Nigeria among women knowledge level on cancer cervix from 2-70.5% (p < 0.0001) after structured group health education [27]; study reported from Vietnamese American women [28] overall knowledge on cancer cervical education program from 30-88% (p < 0.001) and Vietnam rural areas among married women [29] level of knowledge increased from (27.5%-54.3%) in the intervention group (p < 0.05); study conducted in Cameroon [19] women who received the educational intervention had a signi cantly higher knowledge about HPV and cervical cancer in the intervention group 81.6% (p < 0.05)…”
Section: Discussionsupporting
confidence: 85%
“…In this present study, there was an increased knowledge in post-test 83.06% (p < 0.05) after introducing SIM when compared to pre-test 28.83%. Previous studies consistent with the result conducted in Nigeria among women knowledge level on cancer cervix from 2-70.5% (p < 0.0001) after structured group health education [27]; study reported from Vietnamese American women [28] overall knowledge on cancer cervical education program from 30-88% (p < 0.001) and Vietnam rural areas among married women [29] level of knowledge increased from (27.5%-54.3%) in the intervention group (p < 0.05); study conducted in Cameroon [19] women who received the educational intervention had a signi cantly higher knowledge about HPV and cervical cancer in the intervention group 81.6% (p < 0.05)…”
Section: Discussionsupporting
confidence: 85%
“…This finding adds to the growing body of literature that highlights the important role of self-efficacy in cancer prevention behaviors in Vietnamese Americans and other medically underserved Asian American populations. 22,[35][36][37] Second, we found that education was an indirect yet important factor in relation to CRC screening uptake. A higher level of educational attainment was significantly linked to individual CRC-related knowledge, health beliefs, and social norms and, via these associations, was linked to self-efficacy.…”
Section: Discussionmentioning
confidence: 72%
“…This finding adds to the growing body of literature that highlights the important role of self-efficacy in cancer prevention behaviors in Vietnamese Americans and other medically underserved Asian American populations. 22 , 35 - 37 …”
Section: Discussionmentioning
confidence: 99%
“…Households where ≥ 1 screened woman resided tended to be located closer to each other, as compared with the proximity of households with no screened women. Neighborhood-level factors, such as outreach by community health workers, 23 community-based educational programs, 24 , 25 and communication among neighbors, 26 , 27 may play a role in creating pockets of screened households within Amazonian Peru. Neighborhood socioeconomic condition may also affect screening participation.…”
Section: Discussionmentioning
confidence: 99%